Urban residents’ perspectives on eco-city: a second-order confirmatory factor analysis of Khon Kaen, Northeast Thailand - Promphakping, Buapun; Dasri, Rasita; Phatchaney, Kritsada; Promphakping, Ninlawadee; Somaboot, Pornpen; Laotrakul, Songmuang (Frontiers in Sustainable Cities, 2025)
The concept of eco-cities has gained prominence and become a central focus of urban design in recent decades. While theoretical models are well-recognized among policymakers, the extent to which these approaches are understood and embraced by urban residents remains underexplored. Using a quantitative approach, specifically second-order confirmatory factor analysis (Second-Order CFA), this study examined whether the eco-city concept applied by professionals in Khon Kaen, a city located in northeastern Thailand, aligns with residents’ perceptions. A total of 400 residents and stakeholders in Khon Kaen were surveyed using a structured questionnaire. The analysis of urban residents’ perceptions reveals that the economic aspect exerts the most influence on the eco-city concept, followed by environmental and sociocultural aspects. This finding suggests that residents’ perspectives on eco-cities are generally consistent with professional ideas and theoretical models. However, the contribution of latent factors—economic, sociocultural, and environmental—is shaped by complex interactions among the observed factors. The results indicate that transforming the existing economic and environmental structures of the city is challenging, while the sociocultural aspect, from residents’ perspectives, may be more easily addressed. This study recommends prioritizing the retrofitting of social infrastructure and recognizing its contributions to improving both the economy and environment in urban planning.